(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Biological and Medical sciences these days have been advancing toward the new heights and discovery of new methods of diagnose and treatment are paving way for saving the life of people and also in unfolding the mysteries of crimes which marred a society, had they not be resolved. However, the possibility of misuse of such medical sciences cannot be ruled out by those who having hold on them. Under legal profession, a lawyer is supposed to bring before the court all the issues and evils prevalent in the society so that court can deliver a suitable judgment for elimination of evil or resolving the issue. This article explores issues of bioethics and their possible resolution through social sciences.